Lack of virologic suppression is associated with lower HIV-related disclosure stigma in people living with HIV. Issue 8 (2nd August 2020) - Matheu, Michelle; Sunil, Thankam; Castro-Peña, Alexandra; Spears, Camille Elena; Smith, Christopher James; Flores, John Michael; Taylor, Barbara S.
ABSTRACT: Stigma remains a leading barrier to HIV care. To determine the influence of disclosure stigma (DS), fear of disclosing one's serostatus, on virologic suppression, a cross-sectional study was performed at the largest publicly-funded HIV clinic in South Texas. A survey was administered to participants who were: ≥18 years old, living with HIV, and receiving antiretroviral therapy. Surveys included demographics, adherence questionnaire, and a validated HIV-stigma scale with DS as the sum of 10 items ranked 0–3, with score of 30 indicating highest stigma. The primary outcome was lack of virologic suppression (LOVS): most recent HIV-1 RNA > 20 copies/ml. A bivariate analyses examined predictors of DS, dichotomized at the median. Depression score, perceived stress, and lack of friend/family support were associated with DS. Logistic regression models examined the relationship between DS, as a continuous variable, and LOVS. For 275 participants (69% Hispanic), median DS score was 18.5. DS was significantly inversely associated with LOVS (aOR 0.94 per 1 scale point; CI 0.89, 0.99) after adjustment for age, gender/sexual orientation, race/ethnicity, and drug use. The unanticipated inverse association between DS and LOVS highlights the complexity of this relationship. However, the balance of data in this cohort demonstrate an overall negative impact of DS.